Perencanaan Sistem Deteksi Formalin pada Makanan - Yashinta Hardiyani; Sapto Nisworo; Hery Teguh Setiawan (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The use of formalin in food poses serious health risks and there are still many bad people who use formalin as a food preservative, so the author designed and made a formalin detection tool in food without having to be done in a laboratory. The focus of this research is to find out how much ppm the formalin content is in food. The method for research on formalin detection systems in food had designed using experimental techniques. The design of this tool is based on Arduino Nano and uses an HCHO sensor to detect formalin. Peltier is used as a food samples heater to emit steam that the HCHO sensor can detect. In this research, samples without formalin and samples with formalin were tested. The test results obtained that the average error obtained in the test was 8.03% and be obtained the average relative accuracy, which was 91.97%. In tests conducted with laboratory tests without formalin dripping, the test indicated that salted rice anchovies contain formalin by the test sample being purple. This matter that laboratory tests and tests with HCHO sensors indicate the same results.